Changes in physico-chemical parameters during forced-aeration static-pile co-composting of cattle manure with calcium cyanamide - Simujide, Huasai; Aorigele, Chen; Wang, Chun-Jie; Yu, Jun-E; Manda, Bai; Lina, Ma (Journal of Environmental Engineering and Landscape Management, 2014)
The goal of this research was to determine the effect of CaCN2 addition into manure mixed with sawdust on the composting process under forced-aeration static condition, especially on nitrogen (N). The changes in the physical and chemical parameters over the entire composting period were evaluated. The profile of temperature, pH, and NO3 –-N was improved in the piles mixed with 2%, 3% and 4% CaCN2 (the test piles). The NH4 +-N met the limit value accepted for mature compost. Finally, the additive contents of not less than 2% but not more than 3% in CaCN2 were recommended for this system based upon a comprehensive evaluation of the measured parameters.